2022
DOI: 10.11591/eei.v11i1.3337
|View full text |Cite
|
Sign up to set email alerts
|

An open double ring antenna with multiple reconfigurable feature for 5G/IoT below 6GHz applications

Abstract: In this paper, we proposed a hybrid or compound reconfigurable antenna using three PIN diode switching to achieve the different types of reconfiguration: frequency and radiation pattern. Based on an open ring structure with the varied active PIN diodes, the proposed antenna radiation pattern can scan a beam along with one of five directions with the same operating frequency. Depended on the number of active PIN diodes, the antenna operating frequency also can switch to two of six bands which are 1.9 GHz, 2.4/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Two bands, limited return loss in some cases, and more complexity have been offered by the fabricated antenna. Tu et al [21] have shown a compound reconfigurable antenna with three PIN diodes. Multiple functioning frequencies ( 6) with a compact size design has been offered with more complexity due to the biasing circuit of the added PIN diodes.…”
Section: Introductionmentioning
confidence: 99%
“…Two bands, limited return loss in some cases, and more complexity have been offered by the fabricated antenna. Tu et al [21] have shown a compound reconfigurable antenna with three PIN diodes. Multiple functioning frequencies ( 6) with a compact size design has been offered with more complexity due to the biasing circuit of the added PIN diodes.…”
Section: Introductionmentioning
confidence: 99%
“…Reconfigurable antenna is one of the technique used by many researchers to design multiband antennas [11]. Metamaterials are the promising new candidates for designing multiband antennas [12]- [19]. To realise multiband operations fractals have been used [20]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…A single PIN diode provided two modes, resonating at (1) 2.47 and 5.36 GHz, or (2) 3.8 GHz. Another frequency and pattern reconfigurable antenna proposed in [15] is based on three PIN diodes. The radiating element is a double-open-ring patch, and the resonant frequencies lie between 1.9 and 5.6 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available literature concerning antenna reconfiguration characteristics via PIN diodes has so far concentrated on two or more PIN diodes [10][11][12]15,18,[21][22][23][24][25][26]. On the other hand, fewer studies have been published with only one PIN diode [14,27,28].…”
Section: Introductionmentioning
confidence: 99%